Relationship between Urolithiasis and Nutrition in Patients with Urinary Stones in Ardabil City - Ali Hossain Khani; Ali Nemati; Mitra Naser Saead; Shahnaz Hosseinzadeh; Manoochehr Barak (Journal of Ardabil University of Medical Sciences, 2012)
Background & Objectives : Urolithiasis is the third common urinary disease. While, relationship between the urinary stones and diet is known to some extent, but there are controversies about it. The aim of this study was to determine the association between food habit, nutrients intake and kinds of urinary stone disease.   Methods: This cross-sectional and descriptive analytical study was performed on 150 patients (91 male and 59 females) with urinary stone disease in Ardabil during 2008-2009. Data of urinary stones analysis, type of stone in the graph, type of stone, preventive emprise and type of drinking water were recorded. Food data were recorded using 24-hour dietary recalls three days in week and food frequency questionnaires. Data were analyzed using SPSS, Food Processor III software, and ANOVA Statistical program .  Results: Findings showed that the most common and lowest form of urinary stone disease in men and women were calcium oxalate and ammonium phosphate, respectively. There was significant inverse association between beta-carotene intake and the percentage of uric acid stone disease (p<0.05). We observed significant relationship between vitamin A and folacin intake with percentage of uric acid stone disease (p<0.05). There was significant relationship between consumption of cheese and pickles with calcium phosphate stone disease (p<0.05). There was no significant association between other foods and nutrients intake with types of urinary stone disease .  Conclusion: This study showed the consumption of some nutrients including folacin, vitamin A and some foods such as cheese was associated with the incidence of urinary stone disease. Therefore, taking accurate diet could possibly prevent the incidence of urinary stone diseases.